Genetic sources for barley (Hordeum vulgare) breeding in the Volga-Vyatka region - O. N. Shupletsova; I. N. Shchennikova (Труды по прикладной ботанике, генетике и селекции)
Background. The environmental conditions in the northeast of the Russian Non-Black-Soil zone require development of barley cultivars with resistance to higher soil acidity, drought and diseases. Increased productivity in stressful environments was achieved by combining different breeding techniques, including application of cell technologies.Materials and methods. Barley accessions from the unique collection of the N. I. Vavilov All-Russian Institute of Plant Genetic Resources (VIR) served as sources of useful traits. These accessions underwent field- and laboratory-based research at the FASC of the North-East, which was targeted at the main qualities of breeding value: grain yield, growing season duration, and resistance to lodging, diseases and soil stress. Cultivation of callus tissues and regeneration of barley plants were performed in vitro on artificial nutrient media modified by adding selective agents simulating the effect of natural stressors.Results and discussion. After studying the accessions from VIR for various traits of breeding value for the environments of the Volga-Vyatka region, the following breeding sources were selected: cvs. ‘Dina’ (k‑29216, Russia), ‘Andrey’ (k‑30122, Russia), etc. for their earliness; ‘Belogorsky 90’ (k‑29770, Russia), ‘Syabra’ (k‑29917, Belarus), etc. for combined high yield and earliness; ‘Musson’ (k‑30968, Russia), ‘Fenix’ (k‑30835, Ukraine), etc. for lodging resistance; ‘Dina’ (k‑29216, Russia), ‘Medikum’ (k‑30962, Russia), etc. for disease resistance; and ‘Tandem’ (k‑30883, Russia), ‘Novichok’ (k‑30806, Russia), etc. for soil stress resistance. Besides, cvs. ‘Ekolog’ (k‑29417, Russia), ‘Conrad’ (k‑30406, USA), etc. were identified as promising for cellular breeding. General principles regulating selection of initial genotypes for barley tissue culture were formulated. Of practical interest is application of cell-level breeding techniques to cultivars sensitive or moderately resistant to stressors. Accessions from VIR’s collection have been used to develop spring barley cultivars adapted to the cultivation conditions of the Volga-Vyatka region: more than 30 cultivars through hybridization and selection, and 6 cultivars with theuse of in vitro tissue culture.